First microphological and molecular parasitological survey of Benedenia in humpback grouper (Cromileptes altivelis) of Lampung and Situbondo, Indonesia - MUHAMMAD KHOLIQUL AMIIN; SRI SUBEKTI; ENDANG DEWI MASITHAH; DWITHA NIRMALA; MUCHAMMAD YUNUS; MUHAMMAD BROWIJOYO SANTANUMURTI; ARIEF RAHMAN RIVAIE (Society for Indonesian Biodiversity, 2023)
Abstract. Amiin MK, Subekti S, Masithah ED, Nirmala D, Yunus M, Santanumurti MB, Rivaie AR. 2023. First microphological and molecular parasitological survey of Benedenia in humpback grouper (Cromileptes altivelis) of Lampung and Situbondo, Indonesia. Biodiversitas 24: 6858-6867. Capsalid monogenean infections, such as Benedenia, affect grouper aquaculture production. Benedenia will cause lesions and skin damage which will cause fish prices to drop. Secondary infection from bacteria, viruses, and fungi by Benedenia triggers a slow growth rate and even mortality. Benedenia infection on grouper has been conducted in Indonesia, specifically in this study in Lampung and Situbondo. However, molecular identification of this parasite is still lacking. This study aims to determine the microscopic and molecular characteristics of Benedenia from the Hurun Bay waters of Lampung and the North Coast of the Java Sea, Situbondo. The main parameters observed in this study were DNA base sequence, morphology, and phylogenetic tree. Benedenia from Lampung (637 bp) and Situbondo (741 bp) in this study was confirmed by the morphological and molecular close as Benedenia sargocentron with nucleotides. Interestingly, the similarity was less than 98% with B. sargocentron with accession ID JN797597.1 (similarity of 97.15% from Lampung and 86.33% from Situbondo). It could be indicated as a new species of Benedenia. The prevalence of Benedenia in Lampung was 90%, while Situbondo showed 80% with 3 parasite/fish intensity for each location. The outcome of this study is the characteristics of Benedenia from Lampung and Situbondo were similar to B. sargocentron according to morphological and molecular identification. This is the first report of B. sargocentron from Lampung and Situbondo since no molecular identification has been done in those places to confirm their species. Further research by another molecular target apart from 28S rRNA should be needed to identify this parasite more accurately.